An oxidised intrusion-related origin in the controversial Jiaodong gold province (China) for the Shicheng Au-Cu deposit. Issue 1 (1st January 2021) - Elshourbagi, Hadi M.; Fan, Hong-Rui
ABSTRACT: The Shicheng Au-Cu deposit is hosted in the late Early Cretaceous Sanfoshan pluton within the Muping-Rushan (Mu-Ru) metallogenic belt, southeast Jiaodong. The deposit is characterised by Au-Cu bearing quartz-carbonate-sulphide veins that illustrate overprinting sheeted-like and breccia styles. Paragenetically-later veins contain Pb-Zn-(Cu) metal association, suggesting metal zonation at the deposit scale. Quartz from Shicheng shows the cathodoluminescence (CL) textures characteristic of hydrothermal systems with a magmatic influence and exhibits a similar quartz generations sequence. Moreover, this study presents a later overprinting mineralising event, characterised by quartz veins that contain As-rich pyrite, at the Jinqingding deposit in the middle part of the Mu-Ru belt. Jinqingding has a young mineralisation age that overlaps the emplacement age of the Sanfoshan pluton. Quartz from these veins at Jinqingding shows CL textures like those of the Shicheng deposit. The Sanfoshan pluton evolved from highly oxidised, high-K calc-alkaline, I-type magmatism. The early phases of the Sanfoshan pluton have K/Rb, Rb/Sr, and Fe2 O3 /FeO ratios that indicate moderately evolved, less fractionated, and highly oxidised magma, respectively, favouring Au-chalcophile metal association. Therefore, the Shicheng deposit and the overprinting mineralising event at Jinqingding may reasonably represent the products of an oxidised magmatic-hydrothermal system associated with the Sanfoshan-forming magmatism.